LANSKAP BARU TAFSIR SUSASTRA ERA MODERN; STUDI ATAS PENAFSIRAN AL-SYATI DAN IBNU ASYUR - Hamid, Abd; Amin, Ahmad Syaifuddin (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article explores literary interpretation (tafsir susastra), which has been revitalized with new enthusiasm and methodologies in the modern era. Language and literature, as central icons of i‘jāz al-Qur’ān (the inimitability of the Qur'an), have received significant attention since the early period of Qur’anic exegesis. So, where lies the renewal voiced by modern literary interpretation? Using a descriptive-analytical method, this article examines two modern exegetes recognized for employing the al-adabī style and method in their interpretations: Bintu Syāṭi’, through her works al-Tafsīr al-Bayānī li al-Qur’ān al-Karīm and Maqāl fī al-Insān: Dirāsah Qur’āniyyah, and Ibn ‘Āshūr with his work al-Tahrīr wa al-Tanwīr. The researcher concludes that modern literary tafsir emerged as a response to al-tafsīr al-ijtimā‘ī, which was considered to overlook linguistic interpretation. Presenting the Qur’an as a literary masterpiece not only broadens the scope of expressing its i‘jāz but also enriches the depth of interpretive understanding. Methodologically, literature assumes a position both as a method and as an approach/style in interpretation. Modern literary tafsir introduces new elements such as the thematic (mawḍū‘ī) method, elaboration of tartīb nuzūlī (chronological order of revelation), modern literary theories, and attention to social issues—reflecting the influence of the ijtimā‘ī style. The dominance of adab in an interpretation is also shaped by the exegete’s background.